The Impacts of Twitter (X) Diplomacy on Contemporary International Relations - Osondu-Oti, Adaora; Agesin, John Oluwaseun; Olominu, Oluwatomilade (Journal of Contemporary International Relations and Diplomacy, 2024)
There is no gainsaying that social media has become a primary conduit of diplomacy and an arena for government-to-government interactions. In a Twitter diplomacy study conducted in 2018 and published by Burson and Wolfe, at least 97 percent of all 193 UN member states are currently active on Twitter (now rebranded as X), and they are increasingly eliciting public interest. The attention the public gives to world leaders’ tweets illustrates not only the political power of Twitter but also how Twitter challenges conventional diplomatic practices. In formal assemblies, social gatherings, unofficial meetings, and other state-to-state interactions, government officials and policymakers now use Twitter to communicate, transforming diplomacy over time. While it is a fact that social media especially Twitter is rising in popularity as a foreign policy tool, the political impacts of Twitter on international relations need to be interrogated. Thus, this paper analyses the impacts of Twitter (now X) diplomacy on contemporary international relations.